Structure Sensitivity in the Electrocatalytic Reduction of CO2 with Gold Catalysts. (11th February 2019) - Mezzavilla, Stefano; Horch, Sebastian; Stephens, Ifan E. L.; Seger, Brian; Chorkendorff, Ib
Abstract: An understanding of the influence of structural surface features on electrocatalytic reactions is vital for the development of efficient nanostructured catalysts. Gold is the most active and selective known electrocatalyst for the reduction of CO2 to CO in aqueous electrolytes. Numerous strategies have been proposed to improve its intrinsic activity. Nonetheless, the atomistic knowledge of the nature of the active sites remains elusive. We systematically investigated the structure sensitivity of Au single crystals for electrocatalytic CO2 reduction. Reaction kinetics for the formation of CO are strongly dependent on the surface structure. Under‐coordinated sites, such as those present in Au(110) and at the steps of Au(211), show at least 20‐fold higher activity than more coordinated configurations (for example, Au(100)). By selectively poisoning under‐coordinated sites with Pb, we have confirmed that these are the active sites for CO2 reduction. Abstract : Eine goldene Gelegenheit : Gold ist ein aktiver und selektiver Elektrokatalysator zur Reduktion von CO2 zu CO in wässrigen Elektrolyten. Eine Untersuchung der Struktursensitivität von Au‐Einkristallen für die elektrokatalytische CO2 ‐Reduktion zeigt, dass die Reaktionskinetik stark von der Oberflächenstruktur abhängt. Unterkoordinierte Stellen erwiesen sich bei selektiven Vergiftungsexperimenten als aktive Zentren für die CO2 ‐Reduktion.